Revolutionise mental health: the power of digital learning and mental health kit - Mohd Beta, Raja Mayang Delima; Dzulkifli, Nur Nadia; M Antara, Purnomo; Zulkifli, Norfarhana; Zainal Abidin, Nasrullah; Amit, Norani (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Today, wellness, particularly mental, is not just a personal issue but a pressing global concern that needs to be addressed immediately. We live in a digital, fast-paced world, where information is readily accessible to us, with little access to mental health care. Rising levels of mental health concerns and declining availability of trained counsellors have made such a new service necessary (World Health Organization, 2023). With the Mental Health Kit, we are introducing a transformative tool that fuses digital learning with mental health support for those in need, alleviates the burden on professionals, and empowers everyone.